Case report: Using DNA short tandem repeats to confirm nongestational origin of pulmonary choriocarcinoma - da Silva, Filipa Ferreira; Barata, Rita; Rolim, Inês; Carvalheiro, Catarina; Gil, Nuno; Pantarotto, Marcos (Frontiers in Oncology, 2022)
Gestational trophoblastic neoplasias (GTN) are malignant neoplasms that occur in pregnant or recently pregnant women.. Choriocarcinoma (CCA) is a highly aggressive and rare GTN, and cases outside the female genital tract are commonly seen as secondary manifestations of gynecologic disease. In this paper, we describe the case of a 40 years-old female patient with a primary pulmonary CCA who was surgically treated and for whom the confirmation of the primary origin of the tumor was possible using a DNA short tandem repeat genotyping. Distinction between gestational and non-gestational trophoblastic neoplasia is crucial as they require different therapeutic approach and have different prognoses.